Climate change perception, adaptation, and constraints in irrigated agriculture in Punjab and Sindh, Pakistan - Muhammad Mobeen; Khondokar H. Kabir; Uwe A. Schneider; Tauqeer Ahmed; Jürgen Scheffran (Mitigation and Adaptation Strategies for Global Change, 2025)
Pakistan's irrigated agriculture suffers from climate change due to its high exposure to climate~extreme events and the low adaptation of its farming systems. Understanding the human aspects of adaptation decisions in a vulnerable climatic environment is integral for policymakers who want to enhance farmers' adaptive capacity. This study investigates how farmers perceive climate change and what adaptation strategies they consider. Furthermore, we assess the enabling and constraining factors influencing farmers' adaptation decisions. We conducted in-person interviews with 800 farmers across Pakistan's irrigated districts of the Punjab and Sindh provinces. We used a standardized questionnaire to gather primary cross-sectional data, which we analyzed with descriptive statistics. The results show that farmers in the Indus Plain have noticed changes in climate extremes along with longer summer and shorter winter seasons during the last ten years. Most farmers are aware of adaptation options and have already applied some measures. However, the dominant adaptation strategies differ between regions. The farmers in Punjab have primarily adopted crop and farm management practices, while farmers in Sindh have focused on implementing irrigation measures. In both provinces, farmers~regarded rainwater harvesting as the least adopted strategy due to perceived lower effectiveness and practical challenges. The main constraints in the region are a lack of financial resources, water scarcity, and poor soil fertility. Farming decisions are primarily influenced by the availability of financial capital, and specific challenges such as variable rainfall patterns and rising temperatures. Our findings can help policymakers design better policy instruments that account for farmers' perceptions, motivations, and constraints and are thus more effective in promoting sustainable farming practices in Pakistan.
Keywords: 330; Climate change perception; Adaptation; Constraints; Irrigated agriculture; Indus plain; Pakistan